A secured way of keeping medical data efficiently using web farm In the perspective of Bangladesh - Hasan, Rakibul; Biswas, Aditya; Touhid, Md. Touhiduzzaman; Jahan, Umme Nusrat (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.